The pharmacogenomics of carbamazepine-induced cutaneous adverse drug reaction in the South of Vietnam - Nguyen, Ai-Hoc; Sukasem, Chonlaphat; Nguyen, Quy Ngoc; Pham, Hong Tham (Frontiers in Pharmacology, 2023)
Background: The relationship between HLA-B*15:02 and SCARs (Severe Cutaneous Adverse Reactions) was rigorously examined in Japanese, Han Chinese, Thais, and Caucasians. However, the number of studies about this topic in Vietnamese population is still limited and mostly focuses on the North of Vietnam Objective: This study aims to clarify the genetic culprit of SCARs in Vietnamese population, particularly in the South of Vietnam, and to validate our result by a meta-analysis about this topic in Vietnamese. Method: A retrospective case-control study with 37 patients treated with carbamazepine monotherapy. Statistical calculation and meta-analysis were performed by R software. Result: HLA-B*15:02 increases the risk of SJS 12.5 times higher in CBZ-treated patients (p-value=0.017). However, this allele has no impact on MCARs (Mild Cutaneous Adverse Reactions) of CBZ. The number needed to test, and the number needed to genotype is two and nine patients respectively. Conclusion: This study recommends more investigations about the cost-effectiveness of this test to accelerate the protection of Southern Vietnamese from SCARs.